Strongyloides stercoralis infestation mimicking recurrence of ovarian cancer in the liver. Issue 11 (24th August 2022) - Comba, Cihan; Erdogan, Sakir Volkan; Buyukasik, Suleyman; Alis, Esra Ergun; Altinok, Ozge; Gunaldi, Meral
Abstract: Ovarian cancer is the most lethal gynecological cancer and can recur in most cases. Surgery is an option for recurrent ovarian cancer. Parasitic infestation disseminated in an immunocompromised host can be fatal. The case is here presented of a female patient diagnosed with early‐stage ovarian cancer. Chemotherapy was initiated for treatment. At the follow‐up examination, masses in the liver suggestive of recurrence were detected on positron emission tomography computed tomography. Surgery was performed. A Strongyloides stercoralis infestation mimicking relapsing ovarian cancer in the liver was diagnosed.